2013
DOI: 10.1080/15459624.2013.816429
|View full text |Cite
|
Sign up to set email alerts
|

Neither Short-term Sprint nor Endurance Training Enhances Thermal Response to Exercise in a Hot Environment

Abstract: Improvements in fitness from a brief period of physical training may elicit sufficient physiological adaptations to decrease thermal strain during exercise in the heat. This study tested heat adaptation from short-term endurance (ET) and sprint-interval (SIT) training in moderately fit individuals. The ET group (n = 8) cycled at 65% [Formula: see text] for 8 sessions (4 sessions each at 60 and 90 min, respectively) over two weeks, while the SIT group (n = 8) performed repeated 30-s Wingate sprints (resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 35 publications
2
13
3
Order By: Relevance
“…Some studies investigating SIT (McGarr et al, 2014;Trilk, Singhal, Bigelman, & Cureton, 2011) or short-term high-intensity training sessions (Rodas et al, 2000) have found improvements in cardiorespiratory fitness while others (Burgomaster, Hughes, Heigenhauser, Bradwell, & Gibalam, 2005), like our study, have not. The reason for the discrepant findings is uncertain but is likely related to differences in the exercise protocol used and the participants tested.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Some studies investigating SIT (McGarr et al, 2014;Trilk, Singhal, Bigelman, & Cureton, 2011) or short-term high-intensity training sessions (Rodas et al, 2000) have found improvements in cardiorespiratory fitness while others (Burgomaster, Hughes, Heigenhauser, Bradwell, & Gibalam, 2005), like our study, have not. The reason for the discrepant findings is uncertain but is likely related to differences in the exercise protocol used and the participants tested.…”
Section: Discussioncontrasting
confidence: 51%
“…The reason for the discrepant findings is uncertain but is likely related to differences in the exercise protocol used and the participants tested. Participants in the Burgomaster et al (2005) and McGarr et al (2014) studies were ''recreationally active,'' exercising 2-3 times per week (e.g., jogging, cycling, aerobics), yet V O 2peak increased after SIT in the latter but not the former of these two investigations. Participants in the Trilk et al (2011) study were sedentary overweight/obese women, so it is not surprising cardiorespiratory fitness increased in these participants considering that it was low to begin with.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations